2011
DOI: 10.3233/ves-2011-0424
|View full text |Cite
|
Sign up to set email alerts
|

International guidelines for education in vestibular rehabilitation therapy

Abstract: The Barany Society Ad Hoc Committee on Vestibular Rehabilitation Therapy has developed guidelines for developing educational programs for continuing education. These guidelines may be useful to individual therapists who seek to learn about vestibular rehabilitation or who seek to improve their knowledge bases. These guidelines may also be useful to professional organizations or therapists who provide continuing education in vestibular rehabilitation. We recommend a thorough background in basic vestibular scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 96 publications
0
9
0
1
Order By: Relevance
“…This could partly be attributed to the above reasoning, but possibly also to the fact that the vestibular training before surgery (in patients that did not receive intratympanic gentamicin) was performed in a sensory context that was going to change abruptly following surgery. When compensating for an unilateral vestibular loss the individual weighting of remaining senses are recalibrated [32], and specific training after surgery is beneficial [6,21]. Specific vestibular rehabilitation is used to enhance central vestibular compensation mechanisms when they are insufficient or to accelerate recovery [20], and are efficient when the deafferentation is manifest.…”
Section: Discussionmentioning
confidence: 99%
“…This could partly be attributed to the above reasoning, but possibly also to the fact that the vestibular training before surgery (in patients that did not receive intratympanic gentamicin) was performed in a sensory context that was going to change abruptly following surgery. When compensating for an unilateral vestibular loss the individual weighting of remaining senses are recalibrated [32], and specific training after surgery is beneficial [6,21]. Specific vestibular rehabilitation is used to enhance central vestibular compensation mechanisms when they are insufficient or to accelerate recovery [20], and are efficient when the deafferentation is manifest.…”
Section: Discussionmentioning
confidence: 99%
“…The DHI has been one of the most used tools when evaluating the effectiveness of VR in different clinical populations. It was one of the indices recommended by the Barany Society Ad Hoc Committee on Vestibular Rehabilitation Therapy in pre-and post-rehabilitation evaluation 22 . A reduction of greater than or equal to 18 points in DHI scores before and after the intervention is indicative of the intervention being beneficial 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This case study reinforces and illustrates three domain-specific points that have been made previously in the literature: (1) misdiagnosis of dizziness by frontline physicians is a common problem [14, 15]; (2) many vestibular physical (or occupational) therapists are highly experienced in this domain [24] (often more so than generalist or even specialist physicians), publishing articles [25, 26] and teaching courses [27] almost identical to those for physicians specializing in dizziness or vertigo; (3) vestibular PTs must currently play a ‘shadow’ role in diagnosis, because of both scope-of-practice legal constraints and related sociocultural barriers [28]. The importance of these issues are underscored by the high frequency of the problem (>12 million doctor visits per year in the US [6, 7]), the dearth of subspecialty physicians in the US focused on diagnosing vestibular disorders (est.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have identified knowledge gaps [9, 10, 33], evidence-practice gaps [11, 13, 14], frequent diagnostic errors [12, 34, 35], and poor patient outcomes, such as missed strokes [3638]. By contrast, vestibular PTs are extensively trained in these topics [28], not generally covered in medical school or residency. However, dizziness is not unique in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation